Mechanical Properties of High-Nb X80 Steel Weld Pipes for the Second West-to-East Gas Transmission Pipeline Project - Gui-ying Qiao; Xiao-wei Chen; Zhi-en Zhang; Xiu-lin Han; Xu Wang; Bo Liao; Fu-ren Xiao (Advances in Materials Science and Engineering)
The mechanical properties of steel pipe have great effects on the integrality and operation safety of gas transmission pipeline. In order to reduce the cost of the steel pipe, the high-Nb X80 pipeline steels with the different alloying systems have been used in the Second West-to-East Gas Transmission Pipeline Project. Nevertheless, an investigation into the effects of chemical composition on the mechanical properties of steel pipes is lacking. In this work, the chemical composition and mechanical properties of high-Nb X80 grade steel pipes with a diameter of ϕ1,219 mm and a wall thickness of 22 mm, which are coiled by steels manufactured by three mills, have been analyzed. Furthermore, the effects of chemical composition of the steels on the mechanical properties of the pipe body and weld joint were discussed.